Nurse Faculty Enrichment and Competency Development in Oral-Systemic Health - Maria C. Dolce (Nursing Research and Practice)
Nurses are positioned to play a significant role in oral health promotion and disease prevention across the life cycle. Oral health has not been a high priority in nursing practice, and educating nurses about oral health has been inadequate particularly regarding the interrelationship between oral health and overall health. The first step for developing a nursing workforce with core competencies in oral health promotion and disease prevention is to prepare nurse faculty with the requisite knowledge, skills, attitudes, and best practices in oral-systemic health. The purpose of this paper is to present Smiles for Life: A National Oral Health Curriculum as a knowledge framework that nurse faculty can use for faculty enrichment and competency development in oral health across the life cycle. A variety of teaching-learning strategies and resources are provided to assist nurse faculty with integrating oral-systemic health into existing nursing curricula.